Evaluation of two biological matrices for repairing of ventral hernia in bucks - Mahdi, A. K.; H. F. AL-Bayati, Ahmed (The Iraqi Journal of Veterinary Medicine, 2019)
The aim of this study was to estimate the changes in ventral hernia repairing in Iraqi bucks by using two biological matrixes derived from bovine (pericardium and urinary bladder matrix) through histopathological examination. All bucks right lower flank awas prepared surgically, sedation were done by using (2% Xylazine hydrochloride) at a dose of 0.2mg/kg intramuscular, and surgical site anesthetized through an inverted (L) shape local infiltration technique using lidocaine hydrochloride (2%) at a dose of 8mg/kg. Ventral abdominal hernias were induced in (24) bucks through elliptical resection of abdominal muscles to made hernia ring (6-8cm) with avoiding peritoneum perforation. After 30 days of operation bucks were divided into two equal groups. cellular Bovine pericardium group and cellular urinary bladder matrix group. In two groups hernias were treated with only replacement of acellular bovine pericardium and cellular urinary bladder matrix respectively which fixed with interrupted horizontal mattress 2cm far from hernia ring by Polypropylene (No.1) suture material. Histopathological biopsies were taken at 2nd, 8th and 16th week post treatment (4 bucks\ period). Both groups’ successes in reconstruction of large hernia in bucks through prevent recurrent or others post-operative complications. In addition the histopathological examination showed that the acellular urinary bladder matrix superior than acellular bovine pericardium matrix in enhance healing based on acellular urinary bladder matrix role in augment early initiation of inflammatory cells infiltration, fibroblast proliferation and marked collagen deposition, in addition to its early degradation, incorporation and remodeling.